The Effect of Whey Protein Supplements on Acne Vulgaris among Male Adolescents and Young Adults: A Case-Control Study from North of Jordan - Jihan Muhaidat; Almutazballlah Qablan; Faris Gharaibeh; Ghaith H. Albataineh; Nour Abdo; Diala Alshiyab; Firas Al-Qarqaz (Hindawi Limited, 2024)
Background. Young people and athletes willing to gain muscle mass and strength are likely to consume whey protein supplements. The effect of milk as a dietary source of whey protein on acne is still controversial. At the same time, a few studies have suggested an acnegenic impact of whey protein supplements. Objectives. To examine the association of whey protein supplements on acne risk among male adolescents and young adults. Materials and Methods. 201 male teenagers and young adults attending fitness centers in Irbid/Jordan were involved in an observational case-control research; those with acne were deemed cases, and those without acne were considered controls. The primary outcome was a comparison of the proportion of participants in each group who consumed whey protein supplements within the previous three months. Results. 100 acne-afflicted participants were compared to 101 healthy controls with similar demographics, including age, body mass index, educational level, and smoking habits, as well as intake of vitamin B12, corticosteroids, and anabolic steroids. However, considerably more participants in the acne group (47%) were taking whey protein supplements than in the control group (27.7%) (p=0.0047). The significance of this difference was maintained after multivariate analysis. Conclusion. This case-control study provides evidence of a positive association between whey protein consumption and acne risk.